2013
DOI: 10.1016/j.oooo.2012.08.449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-dose extended-release oral azithromycin on anticoagulation status in warfarinized patients

Abstract: Objective: To investigate the possible influence of single-dose 2.0 g azithromycin (AZ-ER) on anticoagulation in patients taking warfarin.Study design: Eighteen consecutive patients receiving long-term stable warfarin therapy were enrolled in this study. AZ-ER was administered 1-hour prior to tooth extraction.The International Normalized Ratio (INR) value was measured prior to AZ-ER administration, during, one-day after, and seven-days after the tooth extraction.Additionally, the azithromycin concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Several reports have investigated the relationship between various antibiotics and INR values [6,9,10,18]. Ghaswalla et al reported that there was a signi cant interaction between time and antibiotics on the INR values of elderly (> 65 years old) patients who were on stable warfarin therapy (AMPC, AZM, levo oxacin…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have investigated the relationship between various antibiotics and INR values [6,9,10,18]. Ghaswalla et al reported that there was a signi cant interaction between time and antibiotics on the INR values of elderly (> 65 years old) patients who were on stable warfarin therapy (AMPC, AZM, levo oxacin…”
Section: Discussionmentioning
confidence: 99%
“…[LVFX]) [18]. AZM in particular, which has a signi cantly long half-life, has been widely discussed in this context [6,10]. Glasheen et al reported that INR value increased beyond the therapeutic range in 31% of AZM cases and 33% of levo oxacin LVFX cases one week after oral administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most previous reports were on long-term treatment cases and cases where oral intake was not possible [1][2][3][4][5]. To our knowledge, there is only one report to have investigated the effects of prophylactic antibiotic administration for tooth extraction on the prothrombin time-international normalized ratio (PT-INR) in patients taking warfarin [6].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the effect of azithromycin (AZM) on INR values in patients taking warfarin [6].…”
Section: Introductionmentioning
confidence: 99%